2009
DOI: 10.1002/jrs.2541
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Raman scattering and infrared spectroscopy of a natural manganocolumbite single crystal

Abstract: A well-ordered natural manganocolumbite single crystal of high quality was used as a prototype for the first determination of the polarized optical phonon modes of materials with the columbite structure. Electron microprobe and X-ray diffraction characterizations determined the chemical formula as Mn 0.60 Fe 0.40 (Nb 0.80 Ta 0.20 ) 2 O 6 , a cationic ordering of 81%, and the crystal structure as belonging to the Pbcn group. Polarized Raman and infrared-reflectivity spectroscopies on oriented samples allowed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Polarized Raman and IR‐reflectivity spectroscopies were used by Moreira et al . to determine the optical phonon dispersions curves of a well‐ordered natural manganocolumbite single crystal of high quality . Remedios et al .…”
Section: Solid‐state Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Polarized Raman and IR‐reflectivity spectroscopies were used by Moreira et al . to determine the optical phonon dispersions curves of a well‐ordered natural manganocolumbite single crystal of high quality . Remedios et al .…”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…[153] Polarized Raman and IR-reflectivity spectroscopies were used by Moreira et al to determine the optical phonon dispersions curves of a well-ordered natural manganocolumbite single crystal of high quality. [154] Remedios et al reported lowtemperature polarized Raman scattering measurements of potassium dihydrogen phosphate: Mn (0.9% wt of Mn) at temperatures ranging from 14 to 300 K over the spectral range 50-1250 cm À1 . [155] They observed that the Raman spectra of undoped and Mn-doped samples at room temperature are very different.…”
Section: Single Crystalsmentioning
confidence: 99%
“…This means that the distance between the two main peaks (E g and A 1g bands) increases with increasing Nb+Ta+Fe content. The intensity of the peak at around 840 cm -1 also significantly increases in the disturbed spectra, which might be related to a stronger influence of (Nb,Ta)-O vibrations (Moreira et al 2010), as can be seen in the CGM spectra (Fig. 12).…”
Section: Raman Analysismentioning
confidence: 60%
“…The Raman spectra of CGM do not show many differences in relationship with the chemical composition, textural contexts, or facies (Fig.12). Band assignments presented below are after the studies ofHusson et al (1977) andMoreira et al (2010). The spectra are marked by a strong vibration at around 880 cm -1 , which is assigned as the (Nb,Ta)O 6 octahedron symmetric stretching vibration (A 1g ).…”
mentioning
confidence: 99%
“…These phenomena are similar as other columbite niobate reported previously. 13,19,20 These results are very important for used as optical devices, which require high quality and optically transparent single crystal. Therefore, the knowledge of the optical phonon behavior is very important and necessary.…”
Section: Experimental Techniquesmentioning
confidence: 94%